2015
DOI: 10.1055/s-0034-1393118
|View full text |Cite
|
Sign up to set email alerts
|

In-class didactic versus self-directed teaching of the probe-based confocal laser endomicroscopy (pCLE) criteria for Barrett’s esophagus

Abstract: For novice trainees, in-class didactic teaching enables significantly better recognition of the pCLE features of Barrett's esophagus than self-directed teaching. The in-class didactic group had a shorter learning curve and were able to achieve 90 % accuracy for their high confidence predictions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…10,11,[13][14][15] interobserver agreement relative to their counterparts receiving self-directed learning. 19,21 We assessed the impact of feedback among the sixteen study observers by Barrett's esophagus showed that following feedback, the overall diagnostic accuracy for dysplasia using pCLE image criteria significantly improved in both didactic and self-directed learning groups. 19 While other similar studies did not find a significant improvement in the accuracy of diagnosis or interobserver agreement following a feedback session for participants, their sample sizes were small, consisting of less than 10 total participants.…”
Section: Discussionmentioning
confidence: 99%
“…10,11,[13][14][15] interobserver agreement relative to their counterparts receiving self-directed learning. 19,21 We assessed the impact of feedback among the sixteen study observers by Barrett's esophagus showed that following feedback, the overall diagnostic accuracy for dysplasia using pCLE image criteria significantly improved in both didactic and self-directed learning groups. 19 While other similar studies did not find a significant improvement in the accuracy of diagnosis or interobserver agreement following a feedback session for participants, their sample sizes were small, consisting of less than 10 total participants.…”
Section: Discussionmentioning
confidence: 99%
“…The reproducibility of luminal CLE parameters has been extensively studied for Barrett’s esophagus, IBD and colorectal polyps. In general, the results have been suitable for a clinical setting with acceptable inter- and intra-observer values 26 27 28 29 30 31 . Recently, the nCLE criteria for pancreatic cystic neoplasms have been evaluated.…”
Section: Discussionmentioning
confidence: 85%
“…In learning to characterize Barrett's esophagus, randomized controlled trials have found no difference between inclassroom training and self-directed training programs for learning to use NBI, but found superiority of inclassroom training when learning to use CLE. 18,19 It remains unclear whether training requirements are different based on the imaging technology or disease application. What is clear is that every person's learning modality of choice and uptake are different.…”
Section: Trainingmentioning
confidence: 99%